Cation Effect on Formation of Preyssler‐type 30‐Tungsto‐5‐phosphate: Enhanced Yield of Na‐encapsulated Derivative and Direct Synthesis of Ca‐ and Bi‐Encapsulated Derivatives12. Issue 15 (3rd November 2015) - Hayashi, Akio; Haioka, Terufumi; Takahashi, Keita; Bassil, Bassem S.; Kortz, Ulrich; Sano, Tsuneji; Sadakane, Masahiro
Abstract: The effect of cations in a reaction mixture for the preparation of the Preyssler‐Jeannin‐Pope type 30‐tungsto‐5‐phosphate [P5 W30 O110 Na] 14– is investigated. Reaction of phosphate and tungstate with a P/W ratio of ca. 3.9 in an acidic aqueous solution without cations selectively leads to the Dawson‐type 18‐tungsto‐2‐phosphate, [P2 W18 O62 ] 6– . Amongst all the alkali cations, only Na + allows formation of the Preyssler‐type polyanion [P5 W30 O110 Na] 14–, with an encapsulated Na + ion, and the product yield can be improved by increasing Na + amount. The presence of Li + ions instead results in the Dawson‐type polyanion [P2 W18 O62 ] 6–, whereas K +, Rb +, and Cs + selectively result in the Keggin‐type polyanion [PW12 O40 ] 3– . An improved synthetic procedure for the Na + ‐encapsulated Preyssler‐ion leading to a higher isolated yield is presented. Furthermore, addition of Ca 2+ and Bi 3+ compounds allows formation of the Ca 2+ ‐ and Bi 3+ ‐encapsulated Preyssler‐type polyanions, [P5 W30 O110 Ca] 13– and [P5 W30 O110 Bi] 12–, respectively. Furthermore, single‐crystal XRD structure of the Bi 3+ ‐encapsulated Preyssler‐type polyanions, [P5 W30 O110 Bi] 12–, is presented for the first time. Abstract :